ANALISIS KINERJA KEUANGAN PT ADIRA DINAMIKA MULTI FINANCE TBK DENGAN ANALISIS RASIO DAN ANALISIS DU PONT - Nur Hari Yansi; Bambang Tetuko (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This research is conducted based on the declining net profit of high in PT Adira Dinamika Multi Finance, Tbk in the period 2013 to2014. This research intents to measure the company performances by using analysis ratio and Du Pont. This research is conducted in February 2015 to June 2015.The method used in this research is quantitative descriptive research method, in which the financial state of the company studied is examined and analyzed using analysis ratio and Du Pont. The sample and the population in this research are financial report of PT Adira Dinamika Multi Finance, Tbk in the period 2013 to 2014.The results of the research of the financial performance of PT Adira Dinamika Multi Finance, Tbk measured using analysis ratio and Du Pont in the period 2013 to 2014 decreased. From the analysis found that too high a load that is not proportional to the increase in sales resulting in ROE to decline. Based on the conclusion above, the implication give to the company is the company must be improve the performance and increasing net profit margin with decrease costs and increase sales. Then the company profit and performace will be better.Keyword : Financial Ratios, Du Pont, Financial Statement